ANALISIS YURIDIS PEMBEBANAN HAK TANGGUNGAN PADA HAK GUNA BANGUNAN DI ATAS HAK PENGELOLAAN - RAHMAD FAHRIANSYAH (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. Abdul Rahim Lubis3. Suprayitno One of the ways to settle bad credit done by a bank is cessie or debt transfer and or hand over (Article 613 of the Civil Code). The case in the ruling of Pekanbaru District Court No.22/Pdt.G/2016/PN.Pbr is a claim by a new creditor (Nelmawati) who has bought the debt from PT Bank Tabungan Negara (Persero) Tbk Pekanbaru against the debtor (Ema Damayanti) who has bad credit to Pekanbaru District Court to permit the transfer of Land Title Certificate which is made collateral of the debtor on behalf of herself. The research problems are related to the legal consequence of the debtor’s collateral if the former creditor transfers the debt by cessie to the new creditor, the efforts to settle the bad credit that can be made by the new creditor related to the prohibition of beding, and the legal analysis of the Ruling of Pekanbaru District Court No.22/Pdt.G/2016/PN.Pbr.Keywords: Debt Transfer, Cessie, Collateral